Visual expression art as a platform for the proclamation of women's equal rights / Ahmad Zaim Zarif Ahmad Zamri, Zahir Alauddin Abd Hamid and Andrialis Abdul Rahman - Ahmad Zamri, Ahmad Zaim Zarif; Abd Hamid, Zahir Alauddin; Abdul Rahman, Andrialis (Universiti Teknologi MARA, Perak, 2024)
This study investigates the efficacy of using creative visuals and their potential to legitimize and represent dynamic imagery in the fight against prejudice and discrimination against women. This study aims to understand more about how abused women feel. This study will demonstrate how groundbreaking it is to capture a woman's emotional speech, which manifests in any form where emotions are expressed, giving women who don't have one a voice and providing them with a secure opportunity to express their deepest thoughts and feelings through visual expression art.